The “third space” in art and therapy. dimensions of art in psychosocial work - Schimpf-Herken, Ilse; Baumann, Till (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Art provides new ways of healing in psychosocial work. It develops experience in the so-called “third space” by generating a gradual approach to the painful experience in which violence is not placed in the foreground –the person concerned is in charge of his/her own healing process. In the same vein, the ‘places of memory’ with a violent past can be transformed into ‘spaces of transference’ (Winnicott) where individuals can become confident as well as empower themselves. ‘Literary metaphor’ allows to experience collective images that strengthen identity and to rebuild the trust or the social relationships violence have destroyed. ‘Scenes of forum theater’ work has to do with the creation of an image of the reality and its transformation into a ‘space of transference’ for real life. The three approaches Paulo Freire Institute has used for its varied experiences between Latin America and Europe show that artistic approaches enable a careful way in which both trust and relationships grow and become a vehicle of social change.